الفكر الديني واثره على بلاد الرافدين - الظاهر رحمن عبد الحسين (Al-Adab Journal, 2019)
The role of the religious institution in the upbringing of society is very clear especially in our Iraqi society where the religious establishment is an integral part of the intellectual, social and political system. Therefore, the influence of religious discourse is negatively or positively on society because the institution is important. Towards good work. Therefore, the letters directed by the institution are considered to represent the shari’a, and since the religious institutions are diverse and different according to the sects, the speech is also different and different. In this sense, if we want to make the Iraqi society a unified society, Which does not mean changing the religious texts because they are fixed, but changing the understanding of the religious text in line with contemporary circumstances and not to bring down the understanding of former scholars who understood the text according to the circumstances they lived a thousand years ago. By changing the Methods in both religious and educational institutions in schools or universities, we will have a tolerant generation and good ties, provided that the media is prevented from spreading the spirit of hatred and negative ideas, and emphasizing the spreading of the spirit of brotherhood and citizenship among the members of Iraqi society and working on establishing the pillars of religion, The prophet Mohammed(pbuh), which will reflect positively on the educational, social and political reality in the country.